The free improvisation game: performing John Zorn’s Cobra - Van der Schyff, D (Virginia Tech Libraries, 2013)
The use of improvisation is wide spread in musical practice around the world. Nevertheless, Western academic circles tend to ignore this ubiquitous activity and have maintained a focus on composition and interpretation. This is beginning to change, however, and the role of improvisation in performance and music education is receiving an increasing amount of attention. This paper contributes to this project by examining the practice of ‘free improvisation’ in a large ensemble context. A rehearsal and performance of John Zorn’s Cobra––a ‘game’ piece for improvisers––is analyzed from a first-person perspective; relevant research in music psychology is considered; and suggestions are made with regard to how we may better understand the nature of musical communication in improvised contexts. Pedagogical applications are also considered.